Obesity rather than regional fat depots marks the metabolomic pattern of adipose tissue: An untargeted metabolomic approach. (18th September 2013) - Hanzu, F.A.; Vinaixa, M.; Papageorgiou, A.; Párrizas, M.; Correig, X.; Delgado, S.; Carmona, F.; Samino, S.; Vidal, J.; Gomis, R.
<x xml:space="preserve">Abstract</x> Objective This study compares the patterns of visceral (VIS) and subcutaneous (SC) adipose tissue (AT)‐derived metabolites from non‐obese (BMI 24‐26 kg/m2) and obese subjects (BMI > 40 kg/m2) with no major metabolic risk factors other than BMI. Methods SC‐ and VIS‐ AT obtained from obese (Ob) and non‐obese (NOb) subjects during surgery were incubated to obtain their metabolites. Differences related to obesity or anatomical provenances of AT were assessed using an untargeted metabolomics approach based on gas chromatography‐mass spectrometry. Results The overall effect of obesity on the metabolite profile resulted more remarkable than the effect of regional AT. Only the depletion of 2‐ketoisocaproic (2‐KIC) acid reached statistical significance for the SC‐AT alone, although it was observed in both depots. Obesity induced more significant changes in several amino acids levels of the VIS‐AT metabolites. On the one hand, higher released levels of glutamine and alanine were detected in the VIS‐ obese AT, whereas on the other, the VIS‐ obese AT presented a diminished uptake of essential amino acids (methionine, threonine, lysine), BCAAs, leucine, and serine. Conclusion This study shows that obesity markedly affects the amino acid metabolic signature of the AT before the clinical onset of other significant metabolic alterations aside from BMI.